Lezecké centrum - Kučerová, Daniela (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Předmětem této diplomové práce je vypracovat dokumentaci pro provedení stavby - novostavby lezeckého centra. Objekt se nachází v severních Čechách, v obci Litoměřice. Při návrhu byl kladen důraz na co nejvyšší kvalitu lezeckého provozu a zázemí pro sportovce. Z tohoto důvodu centrum disponuje dvěmi lezeckými stěnami rozdílného zaměření. Dále zde nalezneme také kavárnu s barem. Druhotně lze prostory využít také pro vzdělání a školení v oblasti výškových prací, bezpečnosti v horách ap. Objekt má 3.NP a 1.PP.

The subject of this diploma thesis is to elaborate documentation for construction - new building of climbing center. The building is located in northern Bohemia, in the village of Litomerice. The design emphasized the highest possible quality for climbing and facilities for athletes also. For this reason, the center has two climbing walls focused on different climbing disciplines. There is also a café-bar. Secondary the space can also be used for education and training in the field of work at heights, safety in the mountains, etc. The building has 3 above-ground floors and a basement.
Climbing centre
Keywords: lezecké centrum; lezecká stěna; železobeton; sportoviště; plochá střecha; Climbing centre; climbing wall; reinforced concrete; sports ground; flat roof